Arbitration in Slovenian Sports - Drnovšek, Katja (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Due to its undeniable advantages, international sports arbitration has become a central mechanism for resolving sports disputes. In Slovenia, however, the legal framework remains limited and fragmented: national legislation regulates arbitration in general terms and sport as a sector, but does not integrate the two, whereas several Slovenian sports federations have recently created or reformed their arbitration mechanisms. The article studies sports arbitration as a multi-layered regime shaped by statutory minimum standards, the regulatory autonomy of sports organisations, and the influence of international federations. It outlines the statutory framework of sports arbitration, analyses the organisational and procedural features of emerging national mechanisms, and highlights practical shortcomings that currently limit the impact of out-of-court mechanisms in sports. It concludes by outlining some conditions under which national sports arbitration could evolve into a credible and effective alternative to ordinary courts while maintaining the legitimate autonomy of sport.